Development of Herbal Mosquito Repellent Lamp from Ginger Lily Oil - บุญเพียร, อำพล; อินธิแสน, ศิริพร; จันทรพล, ปฐมา; อรุโณทยานันท์, วรัญญา (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This research and development aim to 1) Study mosquito preventing of Ginger lily oil 2) Develop repellent lamp with smell of Ginger lily oil and 3) Study satisfaction of repellent lamp with smell of Ginger lily oil using. The sample were 4 healthy volunteer for mosquito preventing study, 8 volunteer for group discussion and 30 volunteer for repellent lamp with smell of Ginger lily oil using. The research tools were group discussion, repellent lamp with smell of Ginger lily oil quality evaluation form and satisfaction evaluation form. Research method include 4 step as 1) Problem analysis 2) Design 3) Trial and 4) Evaluation. Analyze by content consider and mean and standard deviation. The results of this research show 1) Ginger lily oil can prevent Aedes aegypti L. 1.5 hours and Cutex quinquefasciatus Say 4.5 hours 2) Ginger lily oil repellent lamp with oil earthenware, power on - off switch, tungsten light with warm white and 100% ginger lily oil. 3) High satisfaction of repellent lamp with smell of Ginger lily oil using. Thus, repellent lamp with smell of Ginger lily oil can be a choice for herbal product user and develop for commercial as Thai herbal value added and encourage herbal and Thai knowledge.